Association of Coffee and Caffeine Intake With Irritable Bowel Syndrome in Adults - Koochakpoor, Glareh; Salari-Moghaddam, Asma; Keshteli, Ammar Hassanzadeh; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2021)
The aim of this study was to investigate the association between coffee and caffeine intake and odds of IBS and its severity in adult population. In this cross-sectional study, dietary intakes of 3363 Iranian adults were examined using a validated dish-based 106-item Semi-quantitative Food Frequency Questionnaire (DS-FFQ). Coffee and caffeine intake was assessed using the DS-FFQ. IBS was assessed using a modified Persian version of Rome III questionnaire. Binary logistic regression, in which the effect of several potential confounders were controlled for, was used to examine the association between coffee and caffeine intake and prevalence of IBS and its subtypes. To identify the association with severity of IBS symptoms, we applied ordinal logistic regression. After adjustment for potential confounders, we found that individuals who were taking coffee weekly or more had greater odds of IBS (OR:1.50; 95% CI: 1.07-2.11) than those who never drinking coffee. In addition, participants in the top tertile of caffeine intake had 49% greater odds of IBS compared to those in the bottom tertile (OR: 1.49; 95% CI: 1.16-1.90). By gender, this association was observed among women, but not in men (for coffee: OR: 1.50; 95% CI: 1.00-2.57 and for caffeine: OR: 1.50; 95% CI: 1.12-2.02). In addition, a significant positive association was seen between caffeine intake and odds of IBS among subjects with BMI≥25 kg/m2 (OR: 1.76; 95% CI: 1.22-2.53). There was no significant association between coffee and caffeine intake and IBS severity. Coffee and caffeine consumption was associated with increased odds of IBS, in particular among women and those with BMI ≥ 25 kg/m2